Fretting fatigue induced surface cracks under shrink fitted main bearings in wind turbine rotor shafts - Thes Rauert and Jenni Herrmann and Peter Dalhoff and Manuela Sander (Procedia structural integrity, 2016)
This paper deals with the phenomenon of fretting fatigue on the rotor shaft of a wind turbine at the shrink fit of the main bearing. The sensitivity of the rotor shaft for growing cracks that nucleate at the bearing seat is investigated and available approaches of fretting fatigue prediction for shaft-hub and shaft-bearing connections are presented. Their application to the rotor shaft of a wind turbine is assessed and a validation on a full scale and a 1:10 scale rotor shaft fatigue test rig is proposed.
Keywords: crack growth; fretting fatigue; rotor shaft; wear; wind turbine